Education of Zakat, Infaq, and Waqf (ZIWAF) as a Sharia Economic Instrument for Social Welfare in the Community in the Neighborhood of Rizki Bakti Negeri Foundation Pekanbaru - Wali Saputra (Indo Publishing, 2025)
This community service initiative seeks to enhance public literacy and awareness concerning zakat, infaq, and waqf (ZIWAF) as pivotal instruments of the sharia economy, which contribute to the realization of social welfare. Activities were conducted within the context of the Rizki Bakti Foundation in Pekanbaru Negeri, employing a participatory educational approach that included training, simulation, discussion, and digital outreach campaigns. The results from pre-test and post-test assessments indicated a substantial improvement in participants' understanding of ZIWAF concepts and practices. Additionally, this initiative culminated in the formation of a community forum “Friends of ZIWAF”, the distribution of educational materials, and sustainability strategies through advanced training and technological integration. These findings illustrate that ZIWAF education possesses significant potential for reinforcing the community-oriented Islamic economic system. This program stands as a model that can be replicated in other communities as a strategic framework for religious social empowerment within the context of the Ummah economy.